Pelatihan Produksi Video Dokumenter bagi Karang Taruna Handayani Desa Bansari - Wibowo, Joehananto Djoko Teguh; Kundori, Kundori; Heriyanto, Heriyanto; Mintarti, Ari; Hastuti, Sri; Supardi, Supardi (PUAN INDONESIA, 2024)
This study documents the implementation of documentary video production training for Karang Taruna Handayani of Bansari Village, Bansari District, Temanggung Regency, as part of a community service effort to increase community potential through visual media. This training was carried out with the aim of empowering members of Karang Taruna in developing technical and creative skills in video production, as well as to promote the local potential of Bansari Village. The training implementation method includes intensive workshops that include learning the basic theory of video production, hands-on practice in shooting and editing, as well as continuous mentoring from the teaching team. The active participation of Karang Taruna members in all stages of the activity was the key to success in achieving the set objectives. The results of this activity include the production of several documentary videos highlighting various aspects of Bansari Village's life and potential, ranging from natural resources to local cultural activities. These videos not only aim to raise awareness of the village's diversity and beauty, but also as a means to motivate the younger generation to promote and protect their local heritage. In conclusion, this study shows that documentary video production training can be an effective instrument in increasing community participation in local development as well as in strengthening community identity and pride. By applying the skills gained from this training, it is hoped that Karang Taruna Handayani Desa Bansari can continue to play an active role in supporting sustainable development in their village.